Design and Construction of Infrastructure Asset Management Information Systems Using the Rapid Application Development (RAD) Method - Mas Nurul Hamidah (Fakultas Teknik Universitas Bhayangkara, 2024)
The school administration system manages several things, such as the management, storage, and use of facilities and infrastructure items, which have been done traditionally. In contrast, the management must be well structured so that integration with information technology is needed. In previous studies, there were many areas for improvement in the asset information system, one of which was the use of traditional methods such as waterfall which had weaknesses in user flexibility and took a long time to process. Therefore, that a more relevant and accurate method is needed in its completion. SD Khaijah Surabaya built a facilities and infrastructure asset information system using the Rapid Application Development (RAD) method, which offers a more adaptive and interactive solution because it allows the development of rapid prototypes and continuous evaluation of the system. The results of this study show that building an asset management information system can simplify the process of managing infrastructure assets, improve data accuracy, and assist in making decisions related to asset management. The implementation of this system is expected to significantly improve organizational performance in terms of asset management, while system testing using the Black Box method shows accurate results and using the System Usability Scale (SUS) method manages to get a precise score of 80. The average person gives a score of 5 on the assessment of the questionnaire distributed to stakeholders.